Characterization, Serotyping And Antibiogram Of E.Coli Isolated From Fecal Samples Of Kites - Pawade, M.M.; Ingle, V.C.; Tembhurne, P.A.; Budhe, S.D.; Lahade, V.C.; Kumar, Manesh; Kalorey , D.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present study was carried out to study serotypes and drug resistance pattern of E.coli isolated from fecal samples of kites. Out of 40 fecal samples, 14 (35%) isolates revealed morphological, cultural and biochemical characteristics of E.coli.. On serotyping, out of 14 isolates, 3 were non typable, 3 were non-viable and 8 belonged to 6 serogroups viz., O:157(1), O:153(1), O:159(3), O:152(1), O:132(1) and O:2(1). Antibiotic sensitivity pattern showed highest sensitivity towards chloramphenicol, amoxicillin and gentamycin. The isolates were found resistant to ciprofloxacin, norfloxacin, cephalaxein, ceftriaxone, oxytetracline and neomycin.
Keywords: Characterization; Serotyping; E. Coli; Kites